The Effect of Leadership on Employee Performance in Class IIB Kudus Detention Center - Dzaky, Landra Fikri; Kusmiyanti., Kusmiyanti. (Manager : Jurnal Ilmu Manajemen, 2023)
A leader is someone who has the ability to lead, influence the goals of other people and groups so that aniorganizationicanibeiachieved.Unchallengeable aicorrectionalileaderitoday is not only related to how the leaders in all their duties and obligations, but also how theileader is able to manage the performance of the officers under him, including the performance at the Class IIB Kudus Rutan.This study aims to determine the effect of the influence on employee performance. iThe quantitative method used in this research is by using a sampling technique in the form of all employees of the Class IIB Kudus Rutan. The results of this study indicate that theileadership variable has a positive and significant effect on employee performance at theiClass IIB Kudus Rutan. iThis is also evidenced by the results of the coefficient of determination of 0.835 meaning that theiLeadership variable (X) has aniinfluence on Performance (Y) of 83.5%. While the remaining 16.5% is influenced by other factors not included in this or the influence of other variables.